Chromatography assisted in-vitro refolding and purification of recombinant peptibody: recombinant romiplostim a case study - Rana, Sunil; Ughade, Santosh; Kumthekar, Rupali; Bhambure, Rahul (International Journal of Biological Macromolecules, 2023)
In-vitro protein refolding is one of the key rate-limiting unit operations in manufacturing of fusion proteins such as peptibodies expressed using E. coli. Dilution-assisted refolding is the most commonly used industrial practice to achieve the soluble, native functional form of the recombinant protein from the inclusion bodies. This study is focused on developing a chromatography-assisted in-vitro refolding platform to produce the biologically active, native form of recombinant peptibody. Recombinant Romiplostim was selected as a model protein for the study. A plug flow tubular reactor was connected in series with capture step affinity chromatography to achieve simultaneous in-vitro refolding and capture step purification of recombinant Romiplostim. Effect of various critical process parameters like fold dilution, temperature, residence time, and Cysteine: DTT ratio was studied using a central composite based design of experiment strategy to achieve a maximum refolding yield of selected peptibody. Under optimum refolding conditions, the maximum refolding yield of 57.0 & PLUSMN; 1.5 % and a purity of over 79.73 & PLUSMN; 3.4 % were achieved at 25-fold dilution, 15 degrees C temperature, 6 h residence time with 6 mM and 10 mM of cysteine and DTT, respectively. The formation of native peptibody structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structure. The amino acid sequence for the disulfide-linked peptide was mapped using collision-induced dissociation (CID) to confirm the formation of interchain disulfide bonds between Cys7-Cys7 and Cys10-Cys10 similarly for intra-chain disulfide bonds between Cys42-Cys102, and Cys148-Cys206. The developed protocol here is a valuable tool to identify high-yield scalable refolding conditions for multi-domain proteins involving inter-domain disulfide bonds.
Keywords: CE-SDS; Disulfide bonds; In-vitro refolding; Peptibody; Romiplostim